Role of Thyroxine in Minocycline Induced Hypothyroidism in Guinea Pigs (Medical Forum Monthly, 2024)
Background: Minocycline has been used for decades for the treatment of infections caused by a wide range of Gram negative and Gram positive organism. Minocycline has reported to cause hypothyroidism and goiterogenic affects which results in inhibition of thyroid hormones formation.Objective: The thyroid gland is mostly affected by many drugs; these drugs include lithium, amiodarone, nitroprusside, perchlorate, sulfonylurea, minocycline, phenylbutazone, and betadine. The long term use of these drugs is usually associated with hypothyroidism. So the present study was undertaken to observe the role of thyroxin in Minocycline induced thyroidal hormonal disturbance in Guinea pigs.Study Design: Prospective experimental studyPlace and Duration of Study: This study was conducted in the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre (JPMC), Karachi from 10.10.2010 to 10.11.2010.Materials and Methods: 30 adult male Guinea pigs were taken from the animal house weighing between 450-650 Grams. The animals were divided into three groups A, B and C on the basis of treatment given. Group A received control diet, Group B received minocycline (0.02mg/g/day) and Group C received minocycline (0.02mg/g/day) with 0.5ug/g/day thyroxin tablet for 8 weeks at the end of which they were sacrificed, blood sample were taken for serum TSH, T3 and T4.Results: There was highly significant decrease in body weight, increase in both absolute and relative weight of thyroid gland, marked increase in serum TSH, but the serum level of both T3 and T4 were found decreased in guinea Pigs receiving minocycline. Increase in body weight and decrease in both absolute and relative weight of thyroid gland, the level of TSH decreased, while serum levels of T3 and T4 increased in group C animals receiving minocycline with thyroxin.Conclusion:This study was proved that use of thyroxin along with minocycline minimizes the harmful effects of minocycline on thyroid gland to a great extent and thyroxin was effective in preventing the hypothyroidism in experimental Guinea pigs.